Relationship between knee isokinetic muscle strength and countermovement jump height among elite male gymnasts - Ma, Yijie; Zhou, Zixiang; Jin, Rangxi; Wang, Dexin; Chen, Chao (Frontiers in Sports and Active Living, 2025)
IntroductionThis study quantifies the isokinetic knee strength of elite male gymnasts and examines the relationship between concentric extensor strength, limb asymmetry, and countermovement jump (CMJ) height.MethodsA total of 18 elite male gymnasts participated in isokinetic strength testing, assessing concentric and eccentric actions during both extension and flexion of the knee at joint angular velocities of 60°/s, 180°/s, and 240°/s. Relative peak torque (RPT) of the knee flexors and extensors, the functional eccentric hamstring/concentric quadriceps (Hecc/Qcon) ratio, and the inter-limb asymmetries were analyzed. CMJ height was assessed using a contact mat, and the relationship between concentric extensor RPT and limb asymmetries with CMJ height was analyzed using Pearson correlation coefficients analysis.ResultsAt an angular velocity of 180°/s, both an abnormal limb asymmetries in the concentric extensors was observed and the strongest negative correlation with CMJ height (r = −0.638, p < 0.05) was found. At an angular velocity of 240°/s, knee extensor strength demonstrated the strongest correlation with CMJ height (r = 0.962, P < 0.001).DiscussionTherefore, we recommend that gymnasts conduct regular isokinetic strength assessments, particularly focusing on concentric knee extensor strength and limb asymmetries, as they exhibit moderate to high correlations with CMJ height.